Less is more: Mindfulness, portion size, and candy eating pleasure. (January 2023) - Meier, Brian P.; Romano, Allison; Kateman, Samantha; Nori, Rachel
Highlights: We examined eating pleasure and guilt as function of candy (Reese's Peanut Butter Cups) portion size and mindful eating. When eaten normally, pleasure did not differ between a small vs. large portion of the candy. When eaten mindfully, pleasure was higher for a small vs. large portion of the candy. When eaten normally, but not when eaten mindfully, guilt was higher for a large vs. small portion of the candy. An awareness of these effects could encourage people to reduce the portion sizes of the candy they consume. Abstract: Eating candy is pleasurable. Yet, eating candy in large quantities is not recommended. Manufacturers have consistently produced small portion sizes of a variety of candy. While consuming small versus large portion sizes is healthier, do people experience the same amount of pleasure from eating a small portion and does it matter how it is eaten? In a pre-registered study, we examined how candy portion size and mindful eating affected eating-related pleasure. Participants ( N = 301) were randomly assigned to eat a small (113 calories) or large (210 calories) portion of a popular candy, Reese's Peanut Butter Cups. They were also randomly assigned to eat the candy in a regular or mindful manner. We examined eating-related pleasure after consumption. We found that eating pleasure did not differ between portion sizes in the regular eating condition, but in the mindful eating condition, participants experienced more pleasure when eating the small versus large portion. Furthermore, participants experienced more guilt after eating the large versus small portion in the regular eating condition, but portion size did not affect feelings of guilt in the mindful eating condition. An awareness of such effects could encourage people to reduce the portion sizes of the candy they consume.